Mechanical and wear properties of aluminum coating prepared by cold spraying - Yusof S.N.A.; Manap A.; Afandi N.M.; Salim M.; Misran H. (American Institute of Physics Inc., 2023)
In this study, aluminum (Al) powders were deposited onto Al substrates using cold spray to form a coating. The main objective is to investigate and compare the microstructure, mechanical and wear properties of Al coating to that of the Al substrate. The microstructure of the coating and substrate were observed using Scanning Electron Microscope (SEM). Hardness was evaluated using the Vickers Hardness test and wear properties were investigated using a pin-on-disk wear test machine. The elemental composition of the coating and substrate was determined using Energy-dispersive X-ray spectroscopy (EDX). Results showed that the friction coefficient and specific wear rate decreased while wear rate increased linearly with increasing load. It was found that the coating exhibit slightly better mechanical and wear properties compared to the substrate. 2015 AIP Publishing LLC.